Pelaksanaan Perjanjian Pengadaan Barang dan Jasa antara PT Bukit Pembangkit Innovative dengan PT Hafila Daya Utama - Vanissa Ayuningtyas; Albertus Sentot Sudarwanto (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
This study aims to determine the implementation of the goods and services procurement agreement between PT Bukit Pembangkit Innovative and PT Hafila Daya Utama, as well as to determine the obstacles and solutions that occur in the implementation of the goods and services procurement agreement between PT Bukit Pembangkit Innovative and PT Hafila Daya Utama. This research uses empirical legal research. The data used are primary and secondary data. The legal material collection technique used is field research through interviews. This research uses an interactive analysis model with three analysis components, namely data reduction, data presentation, and conclusion drawing. The results showed that the agreement was made to repair damage to the PLTU Banjarsari, then through direct appointment, the company with the best bid price was selected. The first conclusion is that the agreement has been carried out properly in accordance with the provisions in the KUHPerdata and SK Direksi No. 007/SK/DIR-BPI/2021 concerning guidelines for the procurement of goods / services of PT BPI. The second conclusion is that there are several obstacle factors, namely, the process of drafting the agreement, regarding the implementation guarantee, mobilization and labor, the solution is to negotiate, borrow credit, and provide an advance payment for mobilization and consultation with the local Disnaker.